The Expansion View of Thick Concepts. - Kyle, Brent G. (Nous (0029-4624), 2020)
This paper proposes a new Separabilist account of thick concepts, called the Expansion View (or EV). According to EV, thick concepts are expanded contents of thin terms. An expanded content is, roughly, the semantic content of a predicate along with modifiers. Although EV is a form of Separabilism, it is distinct from the only kind of Separabilism discussed in the literature, and it has many features that Inseparabilists want from an account of thick concepts. EV can also give non‐cognitivists a novel escape from the Anti‐Disentangling Argument. §I explains the approach of all previous Separabilists, and argues that there's no reason for Separabilists to take this approach. §II explains EV. §III fends off objections. And §IV explains how non‐cognitivist proponents of EV can escape the Anti‐Disentangling Argument.